Study of Hopcalite (CuMnOx) Catalysts Prepared Through A Novel Route for the Oxidation of Carbon Monoxide at Low Temperature - Subhashish Dey (Bulletin of Chemical Reaction Engineering & Catalysis, 2017)
Carbon monoxide (CO) is a poisonous gas, recognized as a silent killer. The gas is produced by incomplete combustion of carbonaceous fuel. Recent studies have shown that hopcalite group is one of the promising catalysts for CO oxidation at low temperature. In this study, hopcalite (CuMnOx) catalysts were prepared by KMnO4 co-precipitation method followed by washing, drying the precipitate at different temperatures (22, 50, 90, 110, and 120 oC) for 12 h in an oven and subsequent calcination at 300 oC in stagnant air, flowing air and in a reactive gas mixture of (4.5% CO in air) to do the reactive calcination (RC). The prepared catalysts were characterized by XRD, FTIR, SEM-EDX, XPS, and BET techniques. The activity of the catalysts was evaluated in a tubular reactor under the following conditions: 100 mg catalyst, 2.5% CO in air, total flow rate 60 mL/min and temperature varying from ambient to a higher value, at which complete oxidation of CO was achieved. The order of calcination strategies based on activity for hopcalite catalysts was observed to be as: RC > flowing air > stagnant air. In the kinetics study of CuMnOx catalyst prepared in RC conditions the frequency factor and activation energy were found to be 5.856×105 (g.mol)/(gcat.h) and 36.98 kJ/gmol, respectively. Copyright © 2017 BCREC Group. All rights reserved